Non‐alcoholic fatty liver disease predicts type 2 diabetes mellitus, but not prediabetes, in Xi'an, China: a five‐year cohort study. (5th May 2015) - Ming, Jie; Xu, Shaoyong; Gao, Bin; Liu, Guocai; Ji, Yufei; Yang, Fan; Jia, Yunan; Fang, Yujie; Ji, Qiuhe
Abstract Background & Aims Emerging studies have focused the association between non‐alcoholic fatty liver disease (NAFLD) and the risk of type 2 diabetes mellitus (T2DM) but the results were inconsistent. In addition, few studies have put focus on the association between NAFLD and the risk of prediabetes. We aimed to investigate whether NAFLD diagnosed by ultrasonography could predict the risk of future T2DM and prediabetes in Chinese population. Methods The population‐based cohort study held in Xi'an, Northwestern China, was based on China National Diabetes and Metabolic Disorders Survey. During a follow‐up of 5 years, 508 healthy subjects were included as study sample. NAFLD was determined by abdominal ultrasonography. T2DM and prediabetes were diagnosed based on oral glucose tolerance test. Results Of 508 subjects, 97 (19.1%) were diagnosed as NAFLD and 411 (80.9%) were as non‐NAFLD; 20 (3.9%) developed diabetes and 85 (16.7%) developed prediabetes during follow‐up. The incidence of diabetes and prediabetes in the NAFLD group was 20.6 and 51.6 per 1000 person‐years, respectively, whereas that in non‐NAFLD group was 4.9 and 29.2 per 1000 person‐years respectively. Cox proportional hazard regression showed that the multivariable‐adjusted relative risk (RR) of T2DM and prediabetes in the NAFLD group was 4.462 [95% confidence interval (CI): 1.855–10.734, P < 0.001] and 1.642 (95% CI: 0.965–2.793, P = 0.067), respectively, compared with non‐NAFLD group. Conclusions Non‐alcoholic fatty liver disease was a significant predictor for future diabetes, but not for prediabetes, in Xi'an, China. More cohort studies are needed to confirm our findings.